Polarons in Rock-Forming Minerals: Physical Implications - Boriana Mihailova; Giancarlo Della Ventura; Naemi Waeselmann; Simone Bernardini; Wei Xu; Augusto Marcelli (Condensed Matter, 2022)
The existence of thermally-activated quasiparticles in amphiboles is an important issue, as amphiboles are among the main hydrous complex silicate minerals in the Earth’s lithosphere. The amphibole structure consists of stripes of 6-membered TO4-rings sandwiching MO6 octahedral slabs. To elucidate the atomistic origin of the anomalous rock conductivity in subduction-wedge regions, we studied several Fe-containing amphiboles with diverse chemistry by using in situ, temperature-dependent, polarised Raman spectroscopy. The occurrence of resonance Raman scattering at high temperatures unambiguously reveal temperature-activated small polarons arising from the coupling between polar optical phonons and electron transitions within Fe2+O6 octahedra, independently of the amphibole chemical composition. The FeO6-related polarons coexist with delocalised H+; that is, at elevated temperatures Fe-bearing amphiboles are conductive and exhibit two types of charge carriers: electronic polarons with highly anisotropic mobility and H+ cations. The results from density-functional-theory calculations on the electron band structure for a selected amphibole compound with a relatively simple composition are in full agreement with experimental data. The polaron activation temperature, mobility, and polaron-dipole magnitude and alignment can be controlled by varying the mineral composition, which makes amphiboles attractive “geo-stripes” that can serve as mineral-inspired technology to design thermally-stable smart materials with anisotropic properties.